2010
DOI: 10.1161/circresaha.110.217075
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Disruption of Gβγ Signaling Inhibits the Progression of Heart Failure

Abstract: Rationale: Excess signaling through cardiac G␤␥ subunits is an important component of heart failure (HF) pathophysiology. They recruit elevated levels of cytosolic G protein-coupled receptor kinase (GRK)2 to agonist-stimulated ␤-adrenergic receptors (␤-ARs) in HF, leading to chronic ␤-AR desensitization and downregulation; these events are all hallmarks of HF. Previous data suggested that inhibiting G␤␥ signaling and its interaction with GRK2 could be of therapeutic value in HF. Objective: We sought to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 41 publications
10
107
0
Order By: Relevance
“…Moreover, our previous work has already demonstrated that the regulation of G␤␥ signaling by WDR26 is critical for leukocyte migration (16). Recent work has shown that G␤␥ signaling is also involved in numerous pathological conditions such as heart failure and tumor growth and metastasis (5,33). It would be interesting to determine whether aberrant regulation of G␤␥ signaling by WDR26 contributes to these pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous work has already demonstrated that the regulation of G␤␥ signaling by WDR26 is critical for leukocyte migration (16). Recent work has shown that G␤␥ signaling is also involved in numerous pathological conditions such as heart failure and tumor growth and metastasis (5,33). It would be interesting to determine whether aberrant regulation of G␤␥ signaling by WDR26 contributes to these pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…G␤␥-Using a chemical screening approach we previously identified small molecules that bind to G␤␥ subunits and modulate the activity of G␤␥ subunits in cells, in vitro, and in animals (4,(27)(28)(29). The primary screen was based on computationally docking small molecules from the National Cancer Institute diversity library to a peptide/effector/G␣ subunitbinding surface on G␤␥ (4).…”
Section: Binds To G␤␥ and Prevents Binding Of Sigk Peptide Tomentioning
confidence: 99%
“…140 Both ␤ 1 - 141 and ␤ 2 -ARs 58 undergo uncoupling in the failing heart, a process likely explained by receptor phosphorylation 142,143 and increased activity or expression of the inhibitory G protein Gi. 144,145 Strategies for using peptide 146 or small molecule 147 inhibitors of GRK2-mediated receptor phosphorylation have shown promise, and, in addition to restoring receptor function, may improve contractility and reflexively reduce neurohormonal signaling. 146…”
Section: Mechanisms Of ␤-Ar Downregulation and Desensitization Of Resmentioning
confidence: 99%